Pengaruh Tata Kelola Perusahaan, Kinerja Lingkungan, Kinerja Keuangan, dan Nilai Perusahaan Terhadap Green Accounting - Safira Biru Hawa; Muhammad Abdul Aris (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
This study aims to examine the effect of corporate governance, environmental performance, financial performance, and firm value on the implementation of green accounting. A quantitative approach with a positivistic paradigm was applied, utilizing secondary data sourced from annual reports and CSR reports of companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2023 period. The sample was selected using purposive sampling based on specific criteria: companies must have received a PROPER rating, published annual and CSR reports, and provided complete financial data in Indonesian rupiah. Data were analyzed using multiple linear regression with SPSS software, including descriptive statistics, classical assumption tests, and coefficient of determination, simultaneous, and partial tests. The results reveal that among the seven variables tested, only independent commissioners and environmental performance significantly affect green accounting. Meanwhile, institutional ownership, managerial ownership, audit committee, financial performance, and firm value showed no significant impact. This study is limited by its short observation period and the scope of variables. Future research is encouraged to extend the observation period and incorporate other relevant factors, such as stakeholder pressure or government regulation.